Acupuncture for the Elsberg Syndrome Secondary to Varicella-Zoster Virus Infection: a Case Report and Brief Review - Lian-Sheng Yang; Kun Zhang; Dan-Feng Zhou; Shu-Zhen Zheng; Jin Zhang (Medical Association of Pharmacopuncture Institute, 2022)
Elsberg syndrome (ES) is an infectious syndrome presenting with variable signs of acute lumbosacral radiculomyelitis. Its low recognition rate leads to misdiagnosis and incorrect treatment. Thus, some ES patients may develop neurological sequelae. This case described a 74-year-old woman complained of urinary retention, constipation, and sacral numbness after herpes zoster in the perianal area. She was diagnosed with ES and accepted conventional drug treatments and urethral catheterization. The treatment was ineffective; therefore, she accepted electroacupuncture six times and her symptoms completely disappeared, with no recurrence of neurological disorders during 1-year follow-up. This shows that acupuncture is a safe and effective alternative therapy for ES. Nonetheless, further prospective studies are necessary to prove its efficacy in ES.